The Mycology as Forensics Tool - Tranchida, Maria Cecilia (2017)
In a murder case is very common to find a corpse in a grave followed by the human decomposition. In a criminal act, the facts in a legal investigation are not clear enough to help clarify unnatural causes of death by suicide or homicide. Estimating the post-mortem interval (PMI), and mainly in cases where there are no witnesses, is crucial to the investigation process. However, the today study of certain species of fungi found and collected from soil in contact with a rotting human body, contribute to obtain important data useful to estimate the PMI of the victim in crime scene investigation. Dichotomomyces cejpii, Talaromyces trachyspermus, Talaromyces flavus, and Talaromyces udagawae, teleomorphic Ascomycota fungal are the mycobiota currently found and clearly differs to associated mycobiota in control sample and from previously described species Buenos Aires Province, Argentina. Furthermore, additional tests are needed to finally rely on the mycology as a forensic tool.